Comparison of quantitative estimation of intracerebral hemorrhage and infarct volumes after thromboembolism in an embolic stroke model. Issue 6 (29th August 2012) - Eriksen, Nina; Rasmussen, Rune S.; Overgaard, Karsten; Johansen, Flemming F.; Pakkenberg, Bente
<x xml:space="preserve">Abstract</x> Background Strokes have both ischemic and hemorrhagic components, but most studies of experimental stroke only address the ischemic component. This is likely because investigations of hemorrhagic transformation are hindered by the lack of methods based on unbiased principles for volume estimation. Aims We evaluated different methods for estimating the volume of infarcts, hemorrhages, after embolic middle cerebral artery occlusion with or without thrombolysis. Methods An experimental thromboembolytic rat model was used in this study. The rats underwent surgery and were placed in two groups. Group 1 was treated with saline, and group 2 was treated with 20 mg/kg recombinant tissue plasminogen activator to promote intracerebral hemorrhages. Stereology, semiautomated computer estimation, and manual erythrocyte counting were used to test the precision and efficiency of determining the size of the infarct and intracerebral hemorrhage. Results No differences were observed in the infarct volume or amount of bleeding when comparing the three methods of volume estimation. Although semiautomated computer estimation and manual erythrocyte counting provided similar results as the stereological measurements, the stereological method was the most efficient and advantageous. Conclusions We found that stereology was the superior method for quantification of hemorrhagic volume, especially for rodent petechial bleeding, which is otherwise difficult to measure. Our results suggest the possibility of measuring both the ischemic and the hemorrhagic components of stroke, two parameters that may be differentially regulated when therapeutic regimens are tested.